Heavy metal accumulation in leaves of Hydrocharis morsus-ranae l. and biomonitoring applications = Akumulacja metali ciężkich w liściach Hydrocharis morsus-ranae l. i możliwości jego zastosowania w biomonitoringu - Polechońska, Ludmiła; Dambiec, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In present study the concentrations of Hg, Mn, Zn, Fe and Cu in water, bottom sediments and leaves of Hydrocharis morsus-ranae from 11 oxbow lakes of the Odra River were determined by atomic absorption spectrometry. Trace metal concentration in water and bottom sediments were below the geochemical background, indicating no anthropogenic impact in the studied area.
Keywords: metale ciężkie; Hydrocharis morsus ranae; akumulacja metali; biomonitoring; trace metal; metal accumulation